Rajab Bin Yaâkub Dan Aktifitas Keagamannya Di Muara Labuh Solok (1938-1976) - Gusrianti, Yurita; Nurhuda, Ahmad; Yulia, Refni (Pendidikan Sejarah, 2013)
ABSTRACTÂ Â Rajab Bin Yaâkub is a figure and a moslem leader in society at Muara Labuh. He taught Tarekat Naqsabandiyah, religious proselytizing and Tauhid. He taught it because in that time so many person didnât know and understand abaout moeslem religion. However, by teaching Tarekat, he invited the siciety to approach themself to God. In magnigicience moslem religion for the siciety. He do speech in the prayer-house and mosque. Review of this thesis is based on the devolopment of moslem religion problem in Muara Labuh, since 1938 until 1976 which was done by Rajab Bin Yaâkub. he had a direction to missed the Religion. For example believe to one things or a tree, it was called animisme and dinamisme the activity which have done by Rajab Bin Yaâkub is the studies about Naqsabandiyahâs Tarekat, religius proselytizing that have done from home player and returned the society to Tauhid. Formolation problems in this research is how was the bibliography of Rajab Bin Yaâkub and how was his role in religius activities in Muara Labuh. Purpose of this research is to expressed and introdiced Rajab Bin Yaâkub as a moslem leader, also the effort that was done in modification moslem religion in Muara Labuh, Solok.Â Â Key word : In 1938 until 1976, Rajab Bin Yaâkub is a moslem leader which have important roles in Muara Labuh region, Solok.